Controlling histone methylation via trans-histone pathways - Fingerman, Ian M. (2008)
Covalent post-translational modifications of histones have been demonstrated to participate in a wide array of cellular processes, including regulation of gene transcription, gene repression, DNA double strand break repair and mitosis. Regulation of how these covalent modifications, and the implications of this regulation, are currently of great interest. It has been long known that the addition and/or removal of these chromatin modifications are catalyzed by various classes of chromatin modifying enzymes, such as histone acetyltransferases/deacetylases and histone methyltransferases/demethylases. More recently, it has been demonstrated that the addition or removal of these modifications can be dependant upon other existing modifications, both in cis, from within the same histone, or in trans, contributed from another histone. The first trans-histone regulatory event was observed in S. cerevisiae, and influenced histone lysine methylation. This review will give insight into and summarize newly identified trans-histone pathways as a regulatory mechanism for histone lysine methylation.